Veno-arterial extracorporeal membrane oxygenation for respiratory and cardiac support in neonates: a single center experience - Wang, Gang; Li, Qiuping; Zhou, Gengxu; Hong, Xiaoyang; Zhao, Zhe; Meng, Qiang; Feng, Zhichun (Frontiers in Cardiovascular Medicine, 2024)
Objective Extracorporeal membrane oxygenation (ECMO) is an advanced life support that has been utilized in the neonate for refractory respiratory and circulatory failure. Striving for the best outcomes and understanding optimal surgical techniques continue to be at the forefront of discussion and research. This study presents a single-center experience of cervically cannulated neonatal patients on V-A ECMO, a description of our cannulation/decannulation techniques and our patient outcomes. Methods Single center retrospective review of neonates who received neck V-A ECMO support from January 2012 to December 2022. The data and outcomes of the patients were retrospectively analyzed. Results A total of 78 neonates received V-A ECMO support. There were 66 patients that received ECMO for respiratory support, the other 12 patients that received ECMO for cardiac support. The median duration of ECMO support was 109 (32–293) hours for all patients. During ECMO support, 20 patients died and 5 patients discontinued treatment due to poor outcome or the cost. A total of 53 (68%) patients were successfully weaned from ECMO, but 3 of them died in the subsequent treatment. Overall 50 (64%) patients survived to hospital discharge. In this study, 48 patients were cannulated using the vessel sparing technique, the other 30 patients were cannulated using the ligation technique. We found no significant difference in the rates of normal cranial MRI at discharge between survivors with and without common carotid artery ligation. Conclusion We achieved satisfactory outcomes of neonatal ECMO in 11-year experience. This study found no significant difference in early neuroimaging between survivors with and without common carotid artery ligation. The long-term neurological function of ECMO survivors warranted further follow-up and study.